2015
DOI: 10.1128/aem.02931-14
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Salmonella Strains Isolated from Egg Shells and the Layer Farm Environment in Australia

Abstract: bIn Australia, the egg industry is periodically implicated during outbreaks of Salmonella food poisoning. Salmonella enterica serovar Typhimurium and other nontyphoidal Salmonella spp., in particular, are a major concern for Australian public health. Several definitive types of Salmonella Typhimurium strains, but primarily Salmonella Typhimurium definitive type 9 (DT9), have been frequently reported during egg-related food poisoning outbreaks in Australia. The aim of the present study was to generate a pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Although the MLVA profiles of S. Typhimurium isolated in this study and from egg human outbreaks were similar, further studies are required for understanding the invasion potential of these isolates. It was demonstrated that the invasive potential of S. Typhimurium increased after enrichment (31). A hypothesis might be that the invasive potential of S. Typhimurium is influenced by the available favorable environment at the time of invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the MLVA profiles of S. Typhimurium isolated in this study and from egg human outbreaks were similar, further studies are required for understanding the invasion potential of these isolates. It was demonstrated that the invasive potential of S. Typhimurium increased after enrichment (31). A hypothesis might be that the invasive potential of S. Typhimurium is influenced by the available favorable environment at the time of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of these serovars was low in this study. Our previous study indicated that the presence of virulence genes may not necessarily dictate the virulence/invasive ability of Salmonella (31). The PCR results indicated that most of the above-listed serovars harbored virulence genes, but in vivo studies are required to study their virulence potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of Salmonella to survive in different conditions is also based on their ability to use environmental metabolites outside a host (Medrano‐Félix et al, ). However, other studies have demonstrated that some Salmonella strains are invasive with active virulence genes regardless of the isolation origin (McWhorter et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Salmonella infection involves colonization of the small intestine followed by invasion of intestinal epithelial cells (Wallis & Galyov, ). Non‐typhoidal Salmonella serovars exhibit a wide range of in vitro invasion capacity (McWhorter & Chousalkar, ; McWhorter, Davos, & Chousalkar, ; Pang, Lin, Tsai, & Tsen, ; Shah, Zhou, Addwebi, Davis, & Call, ; Shah et al., ) that correlate differences in overall virulence (McWhorter & Chousalkar, ; McWhorter et al., ; Shah et al., ). These differences are likely due to genetic variation within (McWhorter & Chousalkar, ) or differential expression of Salmonella virulence genes (Shah et al., ).…”
Section: Introductionmentioning
confidence: 99%